2019
DOI: 10.1016/j.neuron.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Increased Excitation-Inhibition Ratio Stabilizes Synapse and Circuit Excitability in Four Autism Mouse Models

Abstract: Highlights d Four mouse models of autism share a common increase in E-I ratio in sensory cortex d E-I ratio changes acted to stabilize synaptic depolarization and spiking d Sensory-evoked firing rate in vivo was remarkably normal and sometimes decreased d These findings suggest E-I ratio changes are compensatory in autism

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
310
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(345 citation statements)
references
References 63 publications
(94 reference statements)
33
310
2
Order By: Relevance
“…In part, these problems may arise because some of the observed changes are the result of compensatory neuronal plasticity rather than true FMRP‐dependent biological pathways, and may therefore, differ with age, sex, and genetic background. More systematic future studies of the role of FMRP at different developmental states in multiple auditory nuclei may, therefore, resolve some of these issues …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In part, these problems may arise because some of the observed changes are the result of compensatory neuronal plasticity rather than true FMRP‐dependent biological pathways, and may therefore, differ with age, sex, and genetic background. More systematic future studies of the role of FMRP at different developmental states in multiple auditory nuclei may, therefore, resolve some of these issues …”
Section: Discussionmentioning
confidence: 99%
“…More systematic future studies of the role of FMRP at different developmental states in multiple auditory nuclei may, therefore, resolve some of these issues. 167 Finally, it may be possible to "borrow" useful approaches in other fields for studying FMRP regulation of auditory processing. For example, hearing loss often results in auditory perceptual disruptions, including hyperacusis, where moderate-intensity "everyday" sounds are perceived as intolerably loud or aversive.…”
Section: Directionsmentioning
confidence: 99%
“…Lower excitatory firing was apparent even though mice detected low contrast, static stimuli that drove neural activity far less vigorously than drifting, highcontrast stimuli typical of many studies of mouse V1 (Durand et al, 2016;Michaiel, Parker, & Niell, 2019). This highlights the need to not only compare neural circuit deficits across multiple mouse models of ASD (Antoine et al, 2019), but to also compare across multiple brain states, stimulus sets, and behavioral outcomes. Although we found that differences in arousal could not explain perceptual impairments, neural activity deficits may be more pronounced with behaviorally relevant engagement of neuromodulatory systems, an important topic for future investigations.…”
Section: Discussionmentioning
confidence: 97%
“…However, another study of ASD model mice observed reduced and poorly coordinated excitatory activity in frontal cortex of CNTNAP2 -/-KO mice (Lazaro et al, 2019), but these excitatory activity deficits were not measured during sensory impairments or behavior. A third study suggests that these and multiple other ASD models internally compensate for deficits of excitatory and inhibitory activity, resulting in overall preserved sensory responsiveness (Antoine, Langberg, Schnepel, & Feldman, 2019); crucially, this study also did not measure neural activity deficits during sensory perceptual impairments. It thus remains unresolved if excitatory or inhibitory neural activity deficits underlie simultaneous perceptual impairments in ASD mouse models.…”
Section: Introductionmentioning
confidence: 96%
“…However, evidence for a widespread reduction in inhibition is either indirect or inconclusive. For example, there is evidence for decreased inhibition from genetic models of ASD in mice 7,[9][10][11] , but results in humans remain equivocal 8,[12][13][14][15][16][17] . An alternative is that modulatory processes that suppress neural responses, but do not rely directly on neural inhibition, are either disrupted or differentially engaged in ASD.…”
Section: Introductionmentioning
confidence: 99%